Dakwah berbasis Budaya dalam Masyarakat yang Berubah - Khanna Nailil Muna; Malika Indah Nur Ismaya; Nabila Putri Sayekti; Aisyah Putri Agustin; Nafiah Azzahra; Dheny Prasetya Zulkarmain (Universitas Muhammadiyah Surakarta, 2023)
Dalam tema